The Meaning of Grieving Following Husband Loss among Muslim Women in Surakarta: Covid-19 Context - Fat Chiya Nidaul Chusna; Taufik; Faqihuddin, Ahmad (Universitas Muhammadiyah Surakarta, 2024)
Grieving after losing a husband is a painful experience. This study aims to explore the meaning of grieving following the loss of a husband due to COVID-19 among Muslim women in Surakarta. The study employed a qualitative phenomenological approach, with 4 Muslim women from the city of Surakarta as informants. Data was collected through in-depth interviews, and data analysis was conducted using Interpretative Phenomenological Analysis (IPA). The results of this study show that not all women interpret the death of their husbands as a purely sorrowful experience. In this study, the loss of a husband was interpreted as: (1) A decree of age from God; (2) A good death brings happiness even amidst grief; (3) The husband's death is a temporary separation. The conclusion of this study is that religiosity influences Muslim women's interpretation of the grieving process and fosters inner peace, happiness, hope, optimism, and wisdom.